Probucol Protects Rats from Cardiac Dysfunction Induced by Oxidative Stress following Cardiopulmonary Resuscitation. (30th October 2017) - Xiao, Xu; Hou, Huiyuan; Lin, Victor; Ho, Daisy; Tran, Kyle; Che, Briana; May, Adam; Zhang, Jiancheng; Lu, Zhigang; Lu, Zhongping; Shaw, Peter X.
Abstract : Objective . To investigate the protective effect of probucol on induced cardiac arrest (CA) rats and possible mechanisms. Methods . Sprague Dawley rats were orally administrated with probucol at different dosage or vehicle for 5 days and subjected to a CA model by electrical stimulation, followed by cardiopulmonary resuscitation (CPR). The return of spontaneous circulation (ROSC) rate, antioxidant enzyme activities, and lipid oxidation markers were measured in serum and myocardium. Hemodynamic parameters and myocardial functions of animals were analyzed. Expression of erythroid-derived 2-like 2 (NFE2L2) and Kelch-like ECH-associated protein 1 (KEAP1) in the myocardium were examined with immunohistochemistry. Results . Probucol treatment significantly increased the ROSC rate and survival time of CA-induced rats. After ROSC, levels of oxidation-specific markers were decreased, while activities of antioxidant enzymes were increased significantly in probucol treatment groups. The probucol treatment improves hemodynamic parameters and myocardial functions. These parameter changes were in a dose-dependent manner. In the probucol treatment groups, the expression of KEAP1 was downregulated, while that of NFE2L2 was upregulated significantly. Conclusion . In the CA-induced rat model, probucol dose dependently improved the ROSC rate, prolonged survival time, alleviated oxidative stress, and improved cardiac function. Such protective effects are possibly through regulations of the KEAP1-NFE2L2 system.